2021
DOI: 10.1111/codi.15760
|View full text |Cite
|
Sign up to set email alerts
|

Poor response at restaging MRI and high incomplete resection rates of locally advanced mucinous rectal cancer after chemoradiation therapy

Abstract: Aim Mucinous carcinoma is a histological subtype of rectal cancer and has been associated with a poor response to neoadjuvant chemoradiotherapy (CRT). The primary aim of this study was to analyse the response on MRI of mucinous locally advanced rectal cancer (LARC) after CRT compared to regular adenocarcinoma. Method Patients with LARC (defined as cT4 and/or cN2), who underwent CRT followed by restaging MRI and surgery in two tertiary referral hospitals were retrospectively included in the study. Pre‐ and post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Interesting observations were reported in the article on mucinous tumours by Koeter et al, in which poor response to chemoradiation (CRT) and high rate of resections with a positive circumferential margin 1 . We congratulate the authors on supplementing the literature currently available on the unsatisfactory treatment response of mucinous rectal cancers.…”
mentioning
confidence: 90%
“…Interesting observations were reported in the article on mucinous tumours by Koeter et al, in which poor response to chemoradiation (CRT) and high rate of resections with a positive circumferential margin 1 . We congratulate the authors on supplementing the literature currently available on the unsatisfactory treatment response of mucinous rectal cancers.…”
mentioning
confidence: 90%
“…Compared with common colorectal adenocarcinoma, MCA has entirely distinct clinical, histopathological, and molecular characteristics, as well as an aberrant and aggressive metastatic pattern associated with inadequate response to treatment and worse prognosis 3 . From a clinical perspective, MCA is associated with reduced rates of pathological complete response and tumor downstaging after neoadjuvant chemoradiotherapy compared with non‐mucinous rectal cancer 4,5 . Although immune checkpoint blockade therapy has shown significant efficacy in various solid tumors, MCA patients exhibited a poorer response to PD‐L1 inhibitors than patients lacking the mucinous component 6 .…”
Section: Introductionmentioning
confidence: 99%
“… 3 From a clinical perspective, MCA is associated with reduced rates of pathological complete response and tumor downstaging after neoadjuvant chemoradiotherapy compared with non‐mucinous rectal cancer. 4 , 5 Although immune checkpoint blockade therapy has shown significant efficacy in various solid tumors, MCA patients exhibited a poorer response to PD‐L1 inhibitors than patients lacking the mucinous component. 6 From a histological and molecular perspective, MCA tumor is characterised by extracellular mucin in more than 50% of the lesion.…”
Section: Introductionmentioning
confidence: 99%
“…resection rates of locally advanced mucinous rectal cancer after chemoradiation therapy' [1]. In that study we found that mucinous rectal cancer is associated with a poor clinical response at restaging MRI after chemoradiation therapy, leading to higher rates of involved circumferential resection margins (CRMs) at pathology.…”
mentioning
confidence: 98%